Determination of the spectral dependence for the absorption coefficient of phosphor inorganic microparticles - Khmil’, D.N.; Kamuz, A.M.; Oleksenko, P.F.; Kamuz, V.G.; Aleksenko, N.G.; Kamuz, O.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Developed in the work has been the mathematical model of the composite film, which enables to calculate the wavelength dependence of the absorption coefficient of microcrystals in the phosphor composition. Also, developed has been a new method for determining the spectrum of the absorption coefficient for microparticles of powderlike materials. Being based on this method, obtained has been the wavelength dependence for the absorption coefficient of microparticles of inorganic phosphor ФЛЖ-7-01. At the emission peak of a blue LED (456 nm) their absorption coefficient is close to 684 cm⁻¹.